Assessment of the dynamics of the fibrin monomer and von Willebrand factor in the postoperative period in children with congenital heart disease - V. A. Lastovka; O. B. Gordeeva; R. F. Tepaev; A. R. Bidzhiev (Лечащий Врач, 2021)
Derangements of hemostatic system after cardiac surgery with cardiopulmonary bypass are described in detail, but predictors of thrombotic complication in this group of children are still not detected. It was suggested that fibrin-monomer level and von Willebrand factor concentrations could be used as predictors of thrombosis in infants with congenital heart diseases.